2010
DOI: 10.1177/0894318410362788
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Self-Care Behavior Research on Elders in Thailand

Abstract: Self-care is essential for elderly individuals to maintain their optimal level of health. This meta-analysis was conducted to summarize research findings relating to self-care among the elderly in Thailand. Twenty studies undertaken from 1990 to 2008 were used and 328 effect sizes were computed. Most studies were unpublished master's theses guided by Orem's self-care deficit theory. Data were collected in these studies by face-to-face interviews. Variables with the largest effect sizes encompassed self-concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 22 publications
1
13
2
Order By: Relevance
“…In a Swedish study, it was found that advanced age and lower perceived health were related to weaker self‐care ability (6). This is not quite in line with the results of a meta‐analysis of self‐care behaviour research among older people in Thailand reported by Klainin and Ouannapiruk (7). They found that health status and overall health beliefs were factors with strong relationships with self‐care, while demographic variables like age, sex and education displayed the weakest relationships with self‐care behaviour.…”
Section: Introductioncontrasting
confidence: 69%
“…In a Swedish study, it was found that advanced age and lower perceived health were related to weaker self‐care ability (6). This is not quite in line with the results of a meta‐analysis of self‐care behaviour research among older people in Thailand reported by Klainin and Ouannapiruk (7). They found that health status and overall health beliefs were factors with strong relationships with self‐care, while demographic variables like age, sex and education displayed the weakest relationships with self‐care behaviour.…”
Section: Introductioncontrasting
confidence: 69%
“…Preventive programs targeting the QOL of the Iranian elderly should be considered. A significant improvement in the overall elderly QOL following the Orem model and self-care training was reported (Klainin and Ounnapiruk, 2010;Ware et al, 1993). This study was undertaken to test the benefit of such training on the QOL of the elderly in Masjed Sulaiman.…”
Section: Introductionmentioning
confidence: 99%
“…Individual person or patient to families and communities in collaboration with healthcare professional and healthcare system are involved in self-care. The factors with strong relationships with self-care include health status, overall health beliefs [18], activity level [19] and life satisfaction [20].…”
Section: Chronic Health Carementioning
confidence: 99%